The Kuznets Curve for the Sustainable Environment and Economic Growth - Mukesh Kumar Mishra (ZBW – Leibniz Information Centre for Economics, 2020)
This paper examines different strategies for the protection of the global climate, the environment and Green Growth mechanism for natural resources and scrutinizes the extent to which they meet the transformative requirements of the Paris Climate Agreement and the 2030 Agenda. It analyses the interactions between relevant institutions of global and multi-level environmental governance. It focuses on the legitimacy of respective green mechanisms and their effects on ecosystems and human welfare. It requires that keeping in mind The Kuznets Curves Model Mechanism and reform further to develop the global economic governance system and restructure incentive systems at national level. Crises like COVID-19 show the urgency to promote necessary transformations for our society to survive in the 21st century. It can be a good reminder that in any breakdown, there is always a chance for breakthrough. Pollution and greenhouse gas emissions have fallen across continents as countries try to contain the spread of the new coronavirus. The green economy aims to achieve economic growth and development without an adverse effect on the environment. The environmental Kuznets curve (EKC) hypothesis explains the relationship between economic activity and environmental degradation. Therefore, environmental conservation policies, technological advancement and modern industrial policies are required to make the economic growth of the countries effective in reducing CO2 emissions. There is need for international collaboration among developing and developed countries for fostering green economy and sustainability. We need green growth because risks to development are rising as growth continues to erode natural capital, through the tools of Sustainable Development.
Keywords: Q56; Q57; 330; Sustainable Development; Green Economy; Green Growth; The Environmental Kuznets Curve